Developing Oral Presentation Competence in Professional Contexts: A Design-Based Collaborative Approach - Anil Pathak; Mani Le vasan (International Journal of Evaluation and Research in Education (IJERE), 2015)
The need to develop oral presentation skills with reference to students’ specialized professional contexts has been well-recognised. Attempts have also been made to develop collaboration between engineering faculty and language teaching professionals. In this paper, we describe an experiment where students were given an opportunity to demonstrate their technical know-ho and integrate it with oral presentation skills. The paper discusses specifics of collaboration between the engineering faculty and the language teachers. Specifications for development of a transparent assessment framework have also been elaborated. It is concluded that such design-based approach is more likely to develop skills required of students to perform in competitive communicative environments.